1981
DOI: 10.1159/000265138
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 8-Methoxypsoralen in Ocular Tissues

Abstract: UVA radiation results in the generation of 8-methoxypsoralen (8-MOP) photoproducts which can be permanently retained in the rat and dogfish lenses and retinas as demonstrated by phosphorescence and EPR spectroscopy, autoradiography and radioactivity of labeled products in these tissues. 8-MOP photoproducts also develop in the corneal epithelium but these cells are replaced within 3–4 days. These experiments suggest that photobound 8-MOP products could accumulate in human lenses and in aphakic or young retinas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Experimental studies have demonstrated that methoxsalen is capable of entering ocular tissues, including the crystalline lens (Lerman et al 1980). Theoretically, the photosensitising of the lens fibres induced by methoxsalen could promote the development of cataracts.…”
Section: Methoxsalen (8-methoxypsoralen)mentioning
confidence: 99%
“…Experimental studies have demonstrated that methoxsalen is capable of entering ocular tissues, including the crystalline lens (Lerman et al 1980). Theoretically, the photosensitising of the lens fibres induced by methoxsalen could promote the development of cataracts.…”
Section: Methoxsalen (8-methoxypsoralen)mentioning
confidence: 99%
“…By the 3rd to 4th decade there is a significant level of 440 nm fluorescence while the longer wavelength fluorescence emission requires an additional decade before it shows a similar enhancement [10,11,13,15]. These changes can also be induced and accelerated by in vitro exposure of normal lenses to mono chromatic 300 nm UV radiation [12,17,18]. UV slit lamp densitography measurements on patients whose lenses were judged normal by conven- Fig.…”
mentioning
confidence: 99%
“…8-MOP had been demonstrated in the lens of the enucleated eye of a patient who was given 0.75 mg 8-MOP per kg body weight 12 hours before the enucleation (Lerman et al, 1980). Lerman has also found 8-MOP in the lens in rats and seals (Lerman et al, 1981); this was possible up to 24 hours after administration. If the animals were also exposed to UV-A light, 8-MOP was still demonstrable in the lens 3 weeks later.…”
Section: Discussionmentioning
confidence: 97%